Climate change and crop stress : molecules to ecosystems - Shanker, Arun K.; Shanker, Chitra; Anand, Anjali; Maheswari, M. (Academic Press, 2022)
Climate Change and Crop Stress: Molecules to Ecosystems expounds on the transitional period where science has progressed to 'post-genomics' and the gene editing era, putting field performance of crops to the forefront and challenging the production of practical applicability vs. theoretical possibility. Researchers have concentrated efforts on the effects of environmental stress conditions such as drought, heat, salinity, cold, or pathogen infection which can have a devastating impact on plant growth and yield. Designed to deliver information to combat stress both in isolation and through simultaneous crop stresses, this edited compilation provides a comprehensive view on the challenges and impacts of simultaneous stresses.